The Effect of Economic Growth, Government Spending, and Human Development Index toward Inequality of Income Distribution in the Metropolitan Cities in Indonesia - Alfath Shifa Ghifara; Achmad Nur Iman; Akhmad Kusuma Wardhana; Sulistya Rusgianto; Ririn Tri Ratnasari (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
This study aims to determine and analyze the influence of economic growth, government capital expenditure, and human development index on the inequality of income distribution in Metropolitan Cities in Indonesia. This type of research is descriptive associative research, where the data used is secondary data from 2012 to 2021 obtained from relevant agencies, which were analyzed using the panel data regression method. The findings of this study indicate that the human development index has a negative and significant effect on the inequality of income distribution in Metropolitan Cities in Indonesia, capital expenditures and economic growth have a positive and insignificant effect on the inequality of income distribution in Metropolitan Cities in Indonesia. Taken together, only the human development index has a significant effect on the inequality of income distribution in Metropolitan Cities in Indonesia.